Perkembangan Patologi Onkologi di Bagian Patologi Anatomik Fakultas Kedokteran UGM - SOERIPTO (Univ. Gadjah mada, 1986)
Perkembangan Patologi Onkologi di Bagian Patologi Anatomik Fakultas Kedokteran UGM